Concurrent Cetuximab-based bioradiotherapy versus Cisplatin-based Chemoradiotherapy in the Definitive Management of Favourable Biology Human Papillomavirus-associated Oropharyngeal Squamous Cell Carcinoma: Systematic Review and Meta-analysis. Issue 12 (December 2022) - Swain, M.; Kannan, S.; Srinivasan, S.; Agarwal, J.P.; Gupta, T.
Abstract: Replacing cisplatin with cetuximab concurrently during radiotherapy has been one of the strategies of treatment de-escalation in human papillomavirus (HPV)-associated oropharyngeal squamous cell carcinoma (OPSCC). However, until recently, there were limited data on the efficacy and safety of such an approach. A systematic search of the literature was carried out to identify prospective randomised controlled trials comparing definitive cisplatin-based chemoradiotherapy (CT-RT) versus cetuximab-based bioradiotherapy (BRT) in HPV-positive OPSCC. Overall survival and locoregional control were primary outcomes of interest; rates of acute and late toxicities (≥grade 3) were secondary end points. Outcome data were aggregated using a random-effects model as per Cochrane methodology including risk of bias assessment and expressed as hazard ratio or risk ratio as appropriate with respective 95% confidence intervals. Data from five randomised controlled trials involving 1560 patients with HPV-positive OPSCC were aggregated in the meta-analysis. Cetuximab-based BRT was associated with a significantly increased risk of death (hazard ratio = 2.83, 95% confidence interval 1.22–6.57; P = 0.02) and locoregional relapse (hazard ratio = 2.78, 95% confidence interval 1.77–4.39; P < 0.0001) compared with cisplatin-based CT-RT. Cisplatin was associated with higher rates of acute ≥grade 3 toxicity in terms of acute kidney injury, dry mouth, febrile neutropenia, hearing impairment, nausea and vomiting, whereas dermatitis and acneiform rash were more common with cetuximab. There were no significant differences in overall rates of late ≥grade 3 toxicity (risk ratio = 0.63, 95% confidence interval = 0.36–1.10; P = 0.10). In conclusion, there is moderate-certainty evidence that cetuximab-based BRT leads to inferior efficacy outcomes compared with cisplatin-based CT-RT in the definitive curative-intent management of HPV-associated OPSCC.